(untitled) (Andamios, Revista de Investigación Social, 2013)
This paper presents the academic and ideological profile of Manuel Gamio, considered the father of modern anthropology in Mexico, and one of the main ideologues that marked the twentieth century indigenous, both in Mexico and Latin America. Gamio’s influence was exercised not only in the discussion of ideas, but permeated into public policy and logic of building indigenous institutions orientation. Its formation is exposed in the stream of cultural relativism (or historical particularism) under the tutelage of american anthropologist Franz Boas and his innovations in the field of archeology, ethnography and anthropology in Mexico, and his decisive influence to leave behind the nineteenth-century paradigm “the good Indian is a dead Indian”, emphasizing the need to incorporate the indigenous to modern postrevolutionary state project.